Nitrous Oxide Emissions from Open‐Lot Cattle Feedyards: A Review. Issue 6 (1st November 2016) - Waldrip, Heidi M.; Todd, Richard W.; Parker, David B.; Cole, N. Andy; Rotz, C. Alan; Casey, Kenneth D.
Abstract : Nitrous oxide (N2 O) emissions from concentrated animal feeding operations, including cattle feedyards, have become an important research topic. However, there are limitations to current measurement techniques, uncertainty in the magnitude of feedyard N2 O fluxes, and a lack of effective mitigation methods. The objective of this review was to assess N2 O emission from cattle feedyards, including comparison of measured and modeled emission rates, discussion of measurement methods, and evaluation of mitigation options. Published annual per capita flux rates for beef cattle feedyards and open‐lot dairies were highly variable and ranged from 0.002 to 4.3 kg N2 O animal −1 yr −1 . On an area basis, published emission rates ranged from 0 to 41 mg N2 O m −2 h −1 . From these studies and Intergovernmental Panel on Climate Change emission factors, calculated daily per capita N2 O fluxes averaged 18 ± 10 g N2 O animal −1 d −1 (range, 0.04–67 g N2 O animal −1 d −1 ). This variation was due to inconsistency in measurement techniques as well as irregularity in N2 O production and emission attributable to management, animal diet, and environmental conditions. Based on this review, it is clear that the magnitude and dynamics of N2 O emissions from open‐lot cattle systems are not well understood. Further research is required to quantify feedyard N2 O fluxes and develop cost‐effective mitigation methods. Core Ideas: The magnitude of published N2 O fluxes from open‐lot cattle systems was highly variable. N2O fluxes varied with measurement methods, management, and environmental conditions. Methods to mitigate feedyard N2O emissions are available but have yet to be thoroughly evaluated. Improved animal performance and reducing N intake are best options to reduce feedyard N2O losses.